Environmental, Social, Governance (ESG) As a Tool To Support Smart Sustainable City - Iwona PISZ; Sabina KAUF; Sabina WYRWICH-PŁOTKA (Communications of International Proceedings, 2024)
The purpose of this paper is to provide insight into the implementation of Environmental, Social, Governance (ESG) in cities. The concept of smart city in the context of sustainable development will be presented. Smart city is an innovative concept that integrates digital infrastructure in carefully planned cities to ensure accessibility, environmental friendliness and efficient use of resources. The link between smart city and sustainable city is reflected in the concept of smart sustainable cities. It describes a city whose development is supported by modern technologies and co-created by its residents. In this article, we seek answers to the question of how non-financial reporting can be useful in the development of a smart, sustainable city. In today's world, the concept of smart, sustainable cities is becoming a key goal for cities striving for sustainable development. Environmental, social, and governance (ESG) issues play an extremely important role in this concept, which provides the basis for efforts to create smart and sustainable cities. We will also address how ESG methodology can support city managers in various areas, such as managing urban transportation, organizing waste disposal, or introducing electronic citizen services. In addition, we will discuss the role of smart cities in improving the quality of life of their residents, where ESG, by optimizing environmental, social and economic management solutions, can significantly contribute to the further development of cities. We will present some examples of Polish cities and their approaches to ESG risk management.
Keywords: ESG; CSRD; smart city; sustainable city.